Hygienic assessment of effects of the novel coronavirus on the physical, social, and mental health of individuals from Egypt, United Arab Emirates and other countries from 2020 to 2021 - Tishya Mukherjee; Hamsa Ali Elsayed; Yomna Mousa A. B; Olena Vavrinevych; Andrii Borysenko (Ukrainian Scientific Medical Youth Journal, 2022)
with the onset of SARS-CoV2 virus, which has led to the loss of human capital, economy, and infrastructure, it was crucial to understanding how this virus affects our daily lives. The Novel Corona Virus outbreak was declared a pandemic on 11 Mar. 2020 by The World Health Organization. In 2021, this situation became a crisis when the second and third waves of infection started to arise in various parts of the world. The purpose of this study is the hygienic assessment of the effects of the novel Corona Virus on our physical, social and mental health in Egypt, the United Arab Emirates and other countries from 2020 to 2021. To achieve this goal, we used the following methods. A questionnaire was developed using Google Forms. The format was based on Short Form Health (SF-36) (SURVEY, 2020) and The Johns Hopkins University COVID-19 survey sheet (QUESTIONNAIRE, 2020) in two languages, English and Arabic. We used Simple Random Sampling in our research. The statistical analysis was done using MS Excel and IBM SPSS Statistical Base v.22. The First step of our study was an analysis of challenges faced during the pandemic and ways to overcome them. Determination of the main problems encountered during the pandemic by both males and females. The next step of our research was the analysis of the structure of physical symptoms and health status of COVID-19-infected individuals. It was determined that 23.34 % of participants were infected by the virus. The average was calculated with symptoms: fever 51.4 %, general lack of energy or malaise 51.4 %, loss of sense of smell and taste 60 %, sore throat 54.3 %, vomiting 20 %, diarrhoea 28.57 %, fatigue 45.7 %, stuffy and runny nose or sneezing 57.14 %, chills 40 %, altered consciousness or feeling like it was challenging to stay awake 25.7 %, shortness of breath at rest 37.14 %, shortness of breath when moving (like walking upstairs) 37.14 % and seizure 5.7 %. Next step, our work was dedicated to calculating the Body-Mass index (BMI) country-wise during the pandemic. The average country-wise BMI calculation compared the index before the pandemic and March 2021. Increase in BMI for females in Egypt from (31.1 to 34.6) UAE from (20.1 to 22.6) and other countries from (18.1 to 21.1.). The social stigma toward vaccines between infected and non-infected individuals: infected (n=16) and non-infected (n=35) individuals wants vaccines. 14.2 % infected and 12.2 % non-infected don’t believe in vaccines and 42.7 % infected and 12.2 % non-infected have been vaccinated. The conclusions and trends were studied, evaluated and compared with different articles and the reasons of such progressions were noted and discussed. The two main conclusions drawn from this research were 1) A rise in cases of anxiety, depression and stress during the pandemic and 2) The issue of obesity and weight gain due to home quarantine and remote mode of working. Prospects of further research include studying the effects of the virus in its mutated forms as the virus is evolving. Post-acute sequelae of Covid-19 are also being observed and its study can help us understand the effect of the virus on our body in the long run especially for those who have comorbidities like obesity, hypertension, cancer and type II diabetes.